Benefits of Narrow Business Strategies - Rotemberg, Julio J.; Saloner, Garth (American Economic Review, 1994)
Firms often concentrate on a narrow range of activities and claim to forgo other, apparently profitable, opportunities. This pursuit of narrow strategies is applauded by some academics who study strategic management. We present two related theoretical models in which firms do indeed benefit from pursuing such narrow strategies. In these models, a narrow strategy is beneficial because it enables the firm to motivate its employees to search for ways of increasing the profitability of its core activities. These benefits arise in our model because an incompleteness of contracts precludes offering similar incentives when the firm is involved in many activities.